The Abdolkarim Soroush's Perspective: Relationship of Reason, Freedom, and Islamic Democracy - Fu'ad Arif Noor (Kawanua International Journal of Multicultural Studies, 2021)
Abdolkarim Soroush has emerged as one of the world's leading moderate revisionist thinkers. He and his contemporaries in other Muslim countries formed what might be the equivalent of the Islamic Reformation of Christianity: the period of questioning traditional practices and beliefs that ultimately became an upheaval. Soroush's thoughts include the freedom of Muslims to interpret the Qur'an, the necessity of change in religion, the necessity of freedom of belief, and the compatibility of Islam and democracy. Soroush emphasized the rights of individuals in their relations with government and God, explaining that an ideal Islamic state can only be defined by the belief and will of the majority. The foundation always used by Soroush to explain his political theory is reason. It is the reason behind the modern man to do all his actions. Soroush distinguishes traditional man from modern man is using all his ability to change the world. Traditional people are more passive and deterministic, so they are pessimistic about the life of this world. Reason can not be sustainable if there is no freedom, faith under pressure and compulsion of religion is irrational. One will not be considered religious if he is irrational because it is rational and reason will manifest in the absence of coercion and restraint from religion